2018
DOI: 10.33084/tunas.v3i2.568
|View full text |Cite
|
Sign up to set email alerts
|

Upaya Meningkatkan Hasil Belajar IPA menggunakan Model Pembelajaran Kooperatif Tipe Jigsaw dengan Berbantuan Media Alat Peraga Konkret pada Peserta Didik Kelas V SDN-4 Kasongan Baru Tahun Pelajaran 2016/2017

Abstract: This study aims to (1) find out about the activities of students in learning activities by using a cooperative type jigsaw model assisted with concrete teaching aids (2) knowing the improvement in student learning outcomes in science learning in matter Gravity force, friction force and magnetic force with using a cooperative type jigsaw model assisted with concrete teaching aids in class V of the Kasongan New SDN-4 Academic Year 2016/2017. The type of research is Class Action Research (CAR), the research subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…Tes merupakan suatu alat untuk mengukur tingkat penguasaan dan kemampuan peserta didik secara individu dengan cara memberikan sebuah pertanyaan yang harus diberi tanggapan oleh peserta didik. Tes juga diartikan untuk mengetahui keefektfan produk yang peneliti kembangkan (Fitriana & Diplan, 2018).…”
Section: Tabel 1 Storyboard Gambar Media Keteranganunclassified
“…Tes merupakan suatu alat untuk mengukur tingkat penguasaan dan kemampuan peserta didik secara individu dengan cara memberikan sebuah pertanyaan yang harus diberi tanggapan oleh peserta didik. Tes juga diartikan untuk mengetahui keefektfan produk yang peneliti kembangkan (Fitriana & Diplan, 2018).…”
Section: Tabel 1 Storyboard Gambar Media Keteranganunclassified
“…Menurut (Hamiyah & Jauhar, 2014) Dengan pengimplementasian model pembelajaran jigsaw peserta didik berpartisipasi baik secara mandiri atau bersama Untuk topik pembelajaran setiap dari peserta didik memberikan pendapat dan penjeasan terhadap teman kelompoknya. (Fitriana & Diplan, 2018) yang berpendapat bahwa Peserta didik akan mengembangkan proses brlajar jika mereka belajar dalam suasana terbuka dan santai dengan teman sebaya dalam kelompok.…”
Section: Penerapan Model Pembelajaran Model Jigsawunclassified
“…It can be concluded that information and communication technology as a technology for obtaining, processing, storing, and disseminating various types of information files by utilizing computers and telecommunications was born from strong motivation to create innovation and teachers creativity so it can overcome all laziness and delays in human performance (Fitriana & Diplan, 2018).…”
Section: Information and Communication Technologymentioning
confidence: 99%